Development Book Based on Constructivism for Basic Education in Primary School Teacher Education Program - Anna Mariyani; Wahyu Rikha Rofikhatul Ula (International Journal of Science and Applied Science: Conference Series, 2020)
The objectives of this research are: 1) to develop of book for basic education in the constructivism-based; (2) to investigate the feasibility of book for basic education in the constructivism-based; and (3) the effectiveness of book for basic education in the constructivism-based for the students’ achievement STKIP Muhammadiyah of Blora Central Java. The research used the Research and Development (R&D) method, which referred to the model claim by Thiagarajan (4D), namely: (1) Define; (2) Design; (3) Development; (4) Disseminate. The respondents of book for basic education included field testing respondents consisting 2 validators and 2 practitioners, limited scale main field testing respondents consisting 10 students, and operational field testing respondents consisting of 30 students in class existing learning. The data of research through questionnaire, observation, in-depth interview, and test. The data analysed by using the descriptive qualitative method.